Pengaruh Keamanan dan Kepercayaan Terhadap Keputusan Pembelian di E-Commerce: Studi pada Pengguna E-Commerce Tokopedia di Garut - Muhamad Raihan Zulfikar; Sri Raharso; Ivon Sandya Sari Putri (Transformasi Manageria: Journal of Islamic Education Management, 2024)
The advancement of technology, particularly the internet, has enhanced convenience in human life. This technological development has provided facilities that simplify the execution of online trade transactions, commonly known as e-commerce. Consequently, e-commerce has evolved to create infrastructure for online trade. Tokopedia is one of the e-commerce platforms in Indonesia that offers a variety of products and services for buyers, facilitating transactions between sellers and buyers through its application or website. Trends indicate a decline in Tokopedia's e-commerce transactions in Garut Regency from February to May 2024. At the beginning of 2024, Tokopedia faced news that caused losses for some of its users in Garut Regency, impacting the security and trust aspects of purchasing decisions on Tokopedia. The aim of this study is to determine the extent of the influence of security and trust on consumer purchasing decisions in Garut Regency on Tokopedia's e-commerce platform. This research uses a descriptive quantitative method with non-probability sampling techniques and a purposive sampling sub-technique. The study population consists of Tokopedia e-commerce users spread across Garut City, with a sample size of 256 respondents. The results indicate that security and trust have a significant and positive influence on purchasing decisions, with an impact of 52.7%.